Forensic insight into sudden maternal death from spontaneous uterine rupture in the third trimester: an autopsy-based case report - Kumar, Munesh; Tandon, Shubhangi; Sharma, Vijay; Tandon, Sarvesh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Spontaneous rupture of the uterus remains a severe obstetric complication in many developing nations, posing a significant threat to both maternal and fetal outcomes. In India, it continues to contribute to approximately 5-10% of maternal deaths, primarily due to the high incidence of unregistered or emergency pregnancies, particularly among women from rural regions with limited access to antenatal care. While rupture of a previously scarred uterus is more commonly reported, spontaneous rupture of an unscarred uterus is an uncommon occurrence. Identified risk factors for such ruptures include grand multiparity, abnormal placentation, and congenital uterine malformations. We are reporting an autopsy-based case of sudden, unexplained death of a 40-year-old full-term pregnant lady, who was G7P6L6, with all previous normal deliveries, in which multiparity was the predisposing factor of spontaneous uterine rupture.